High Involvement Work System and Performance of Indonesian Banking Sector - Nazaruddin Malik; Mudrifah Mudrifah (Universitas Muhammadiyah Malang, 2020)
This research aims to analyze the effect of High Involvement Work System (HIWS) and technologies adaption on the performance in Indonesian banking sector and also determine whether the perceived leadership behavior successfully moderating the effect of HIWS and technologies adaption on the banking sector performance in Indonesia. The data of 96 respondents were conducted by questionnaire that measured using the 1 (totally dissagree) to 5 (totally agree) Likert score and analyzed using the associative method using PLS software. The result indicates that the application of HIWS in the banking sector has a positive but not significant effect on the performance. While the test results state that technologies adoption significantly influences positive performance in the banking sector. For moderation variables in the form of perceived leadership behavior weaken the influence of HIWS on performance, otherwise, it strengthen the influence of technology adoption on the performance of Indonesian banking sector.